Charcot-Marie-Tooth disease with pyramidal features due to a new mutation of EGR2 gene. - Fusco, Carlo; Spagnoli, Carlotta; Salerno, Grazia Gabriella; Pavlidis, Elena; Frattini, Daniele; Pisani, Francesco; Bassi, Maria Teresa (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Childhood-onset peripheral neuropathies are often of genetic origin. Charcot-Marie-Tooth (CMT), is considered the commonest neuromuscular disorder. Due to its high clinical heterogeneity, especially in the pediatric age, the co-existence of central and peripheral symptoms and signs does not necessarily rule out a diagnosis of hereditary peripheral neuropathy. Methods: We describe the clinical, neurophysiological and genetic findings in a teen-age patient evaluated for acquired toe-walking and progressive difficulties in walking since the age of 5. Genetic testing was carried out with a targeted NGS panel. Identified variants are analyzed using Variant Studio program (Illumina). Rare variants and variants considered as pathogenic were analyzed by Sanger direct sequencing. Results: The coexistence of peripheral and pyramidal signs in the lower limbs, the absence of a significant pre/perinatal history, the unremarkable brain and spine MRI, together with the presence of a sensory-motor polyneuropathy in all four limbs, prompted the execution of genetic investigations with an NGS panel covering hereditary spastic paraplegias, motor neuron disease and Charcot-Marie-Tooth. We identified a previously undescribed variant (c.1142G>T, p.Arg381Leu) in the EGR2 gene. Conclusions: ERG2 gene has been described as a cause of various phenotypes, including a rare autosomal dominant form of CMT (CMT type 1D) representing approximately 1% of all CMT subgroups. We describe a novel pathogenic variant in EGR2 gene leading to the development of a complex association of peripheral and central neurological signs, underscoring the genetic and clinical heterogeneity of hereditary neuropathies of pediatric onset.